Feeding Broilers on Finisher Diet of Low Trace Mineral Levels and its Effect upon Performance, Carcass Characteristics, Mineral Excretion and Net Profit - Mohamed , M.A.; Hassan, H.M.A.; Youssef, Amani W.; Gad, Sawsan M. (International Journal of Poultry Science, 2015)
Growth experiment was carried out to examine the effect of feeding broilers on finisher diet (23 to 39 days of age) contained low levels of trace mineral premix. Two hundred male Ross broiler chicks were divided into four treatment groups, five replicates each. Four corn-soybean finisher diets were formulated to cover all the nutrient requirement and the trace mineral premix (TMP) was added at 100, 75, 50 or 25% of the recommended level. Performance, carcass characteristics, tibia ash, mineral excretion and economic efficiency were measured. The results showed that reducing trace mineral content in finisher diets did not affect chick performance (p>0.05). There were no significant differences in body weight gain, feed intake and feed conversion ratio. Also, carcass characteristics and tibia ash content did not significantly affect by lowering level of dietary TMP. Mineral excretion significantly (p